STUDI KEPEMIMPINAN TRANSFORMASIONAL, BUDAYA ORGANISASI DAN DAMPAKNYA TERHADAP KOMITMEN AFEKTIF Studi pada Pegawai Dikantor Dinas Pariwisata Dan Budaya Kota Yogyakarta - Ovaldus Hardianto Ngambur (JURNAL ILMIAH EDUNOMIKA, 2021)
This study aims to determine and analyze the influence of transformational leadership and organizational culture and its impact on affective commitment to employees of the Yogyakarta City Culture and Tourism Office. The results of this study are expected to be used as a material or frame of reference for employees of the Yogyakarta City Tourism and Culture Office in increasing affective commitment to the installation. The research method used in this research is a questionnaire, which is a data collection technique by means of a series of questionnaires that have been compiled for respondents to be answered and assessed, the sampling technique uses probability sampling, which is a technique that provides equal opportunities or opportunities for each element or member of the population. to be selected to be the sample. Data collection will be carried out in 2021. The data analysis technique uses Path Analysis. The results of the descriptive analysis show that in general transformational leadership and organizational culture and affective commitment in the tourism and culture office of Yogyakarta are in good categories. The results of the verification analysis show that transformational leadership and organizational culture have a positive and significant effect on the affective commitment of employees in the tourism and culture office of the city of Yogyakarta. Keywords: Transformational Leadership; Organizational Culture; Affective Commitment.